2021
DOI: 10.3892/ijmm.2021.5077
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA LINC01748 exerts carcinogenic effects in non‑small cell lung cancer cell lines by regulating the microRNA‑520a‑5p/HMGA1 axis

Abstract: The important functions of long non-coding RNAs in the malignancy of non-small cell lung cancer (NSCLC) has been increasingly highlighted. However, whether LINC01748 functions in a crucial regulatory role still requires further research. The aim of the present study was to investigate the biological roles of LINC01748 in NSCLC. Furthermore, different experiments were utilized to investigate the mechanism of action of LINC01748 in 2 NSCLC cell lines. Reverse transcription-quantitative PCR was used to measure mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Growing evidence has ascertained that lncRNAs are involved in the progression and metastasis of NSCLC and were associated with the immune pathway ( Pang et al, 2021 ). LINC01748 exerted carcinogenic effects in NSCLC cell lines by regulating the microRNA-520a-5p/HMGA1 axis ( Tan et al, 2022 ). lncRNA-SChLAP1 was verified to induce NSCLC progression and immune evasion by regulating the AUF1/PD-L1 pathway ( Du et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has ascertained that lncRNAs are involved in the progression and metastasis of NSCLC and were associated with the immune pathway ( Pang et al, 2021 ). LINC01748 exerted carcinogenic effects in NSCLC cell lines by regulating the microRNA-520a-5p/HMGA1 axis ( Tan et al, 2022 ). lncRNA-SChLAP1 was verified to induce NSCLC progression and immune evasion by regulating the AUF1/PD-L1 pathway ( Du et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, AC145207.5 (RP11-498C9.15) plays a pivotal role in rheumatoid arthritis by modulating both miRNAs and gene expression ( Dolcino et al, 2019 ). Moreover, LINC01748 regulates the miRNA-520a-5p/HMGA1 axis to exert carcinogenic effects in non-small cell lung cancer ( Tan et al, 2022 ). Collectively, the AC145207.5/LINC01748-miR-101-3p- CAMSAP1 axis has been identified as a potential regulatory pathway in LIHC.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoresistance is a challenging issue in cancer therapy. Numerous studies have shown that HMGA1 can be involved in drug resistance to cisplatin, gefitinib, 5-FU, gemcitabine, and trabectedin in a TGF-β-, pathway-, microRNA-, and lncRNAregulated manner in a variety of tumours, such as NSCLC, gastric cancer, ovarian cancer, glioblastoma, cholangiocarcinoma, colorectal cancer, thyroid cancer, and liposarcoma [65,93,142,[148][149][150][151][152][153]. More importantly, HMGA1 silencing can also reduce self-renewal, dryness and spheroid formation in glioblastoma and colorectal cancer, increasing drug sensitivity [95,142].…”
Section: Hmga1 and Chemoresistancementioning
confidence: 99%